A Consecutive Ring-Expansion Strategy towards the Macrocyclic Core of the Solomonamide Natural Products - Yang, Zhongzhen; Swanson, Christopher R. B.; Unsworth, William P. (Synlett, 2022)
A synthetic strategy based on the application of three consecutive ring-expansion reactions has been used in the synthesis of analogues of the macrocyclic core of the solomonamide natural products. Starting from a simple, readily available tetrahydrocarbazole, oxidative ring expansion is followed by two further 3- and 4-atom ring-expansion reactions, enabling the insertion of amino acid and hydroxy acid derived linear fragments into 15- to 17-membered-ring-enlarged macrocyclic products.
Keywords: macrocycles; medium-sized rings; ring expansion; natural product analogues; lactams; lactones; solomonamides